'Being traitors': post-war Greece in the experience of Jewish partisans. Issue 2 (3rd April 2017) - Králová, Kateřina
Abstract: As a result of political developments, silence about Jewish resistance in post-war Greece persisted for decades. In my article, I focus on the post-war fate of Jewish partisans in the context of the Greek Civil War and the emerging East–West conflict. After liberation, many partisans in Greece were stigmatized and even tried as communists. In the 1980s, when Athens shifted towards socialism, Jewish survivors began to speak up regarding their involvement in the left-leaning resistance (EAM/ELAS). Based on archival research and oral testimonies, I explore how former Jewish partisans reflected on their EAM/ELAS participation, in which way they came to terms with the imminence of post-war persecution and which attitudes were applied in the case of arrests. In this way, this study may contribute not only to a better understanding of post-the First World War Greece but also towards identity politics and memory studies in general.